2020
DOI: 10.1155/2020/3163629
|View full text |Cite
|
Sign up to set email alerts
|

Prokineticin 2 (PK2) Rescues Cardiomyocytes from High Glucose/High Palmitic Acid-Induced Damage by Regulating the AKT/GSK3β Pathway In Vitro

Abstract: Prokineticin 2 (PK2) is a small 8 kDa protein that participates in many physiological processes, such as angiogenesis, inflammation, and neurogenesis. This experiment investigated the effect of PK2 on high glucose/high palmitic acid-induced oxidative stress, apoptosis, and autophagy in cardiomyocytes and the AKT/GSK3β signalling pathway. H9c2 cells were exposed to normal and high concentrations (33 mM) of glucose and palmitic acid (150 μM) with or without PK2 (10 nM) for 48 h. Reactive oxygen species were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…A study by Ribeiro et al revealed that HG inhibited autophagy to accelerate cartilage degradation, and pharmacological autophagy activation inversely attenuated the harmful effects on chondrocytes 22 . Adversely, other studies reported that autophagy as a response mechanism was upregulated to offer protection against HG-induced apoptosis and senescence, which means completely reverse result 21 , 26 , 41 . In the present study, the results of in vitro experiments revealed that autophagy levels changed dynamically with increase in glucose concentration.…”
Section: Discussionmentioning
confidence: 98%
“…A study by Ribeiro et al revealed that HG inhibited autophagy to accelerate cartilage degradation, and pharmacological autophagy activation inversely attenuated the harmful effects on chondrocytes 22 . Adversely, other studies reported that autophagy as a response mechanism was upregulated to offer protection against HG-induced apoptosis and senescence, which means completely reverse result 21 , 26 , 41 . In the present study, the results of in vitro experiments revealed that autophagy levels changed dynamically with increase in glucose concentration.…”
Section: Discussionmentioning
confidence: 98%
“…In the same work, in an in vivo animal model of myocardial infarction, induced by coronary ligation, the authors demonstrated that PKR1 gene therapy preserved the myocardial function by blocking the apoptosis and stimulating angiogenesis (Urayama et al, 2007;Urayama et al, 2008). In line with this data, recent studies have confirmed that PROK2 exerts its protective role on cardiomyocytes by activating the Akt/mTOR (Su et al, 2020) and AKT/GSK3β (Yang et al, 2020) signaling pathways.…”
Section: Pks Involvement In the Response To Pathological Insults Oxidmentioning
confidence: 70%
“…Oxidative stress Neurotoxic -Primary cortical cell cultures -Hypoxia and ROS: ↑ PROK2 mRNA mainly in neurons (Cheng et al, 2012) -in vivo stroke models -Ischemic cortex and striatum: ↑ PROK2 mRNA (Cheng et al, 2012) -PROK2 i.c.v. injection after stroke: ↑ infarct volume (Cheng et al, 2012) -PKRs antagonist: ↓ infarct volume, ↓ central inflammation and improves behavioral outcome (Cheng et al, 2012) Neuroprotective -in vitro model of focal cerebral ischemia -Bv8: ↓ the OGD-induced necrotic neuronal death in cortical cultures and hippocampal slices activating ERK, Akt and GSK3-β pathways (Landucci et al, 2016) -PKRs antagonist reverts the Bv8 effects (Landucci et al, 2016) -in vitro model of ischemic tolerance (NMDA preconditioning) -Hippocampal slices: ↑ PROK2, PKR1 and PKR2 mRNA and protein (Landucci et al, 2016) -PKRs antagonist: ↓ PROK2 protein in hippocampal slices (Landucci et al, 2016) -H9c2 cardiomyocytes cell line from rat heart -PROK2 treatment or PKR1 overexpression: ↓ oxidative stress-induced apoptotic cell death activating the Akt/mTOR and AKT/GSK3β pathways (Urayama et al, 2007;Su et al, 2020;Yang et al, 2020) Beta amyloid Neurotoxic -Primary cortical cell cultures -Aβ 1-42 : ↑ PROK2, PKR1 and PKR2 mRNA and protein levels in neurons and astrocytes (Severini et al, 2015) -Bv8, at pM concentrations, ↑ neuronal apoptosis (Severini et al, 2015) -PKRs antagonist: ↓ Aβ-and Bv8-induced neuronal apoptosis (Severini et al, 2015) and ↓ kainate-evoked current increase Aβ-induced (Caioli et al, 2017) -Tg2576 transgenic mouse model of AD↓ -Cortex and hippocampus: ↑ PROK2 mRNA (Lattanzi et al, 2019) -PKRs antagonist: ↓ LTP impairment in hippocampal slices (Severini et al, 2015) -in vivo non-transgenic rat model of AD -Aβ 1-42 i.c.v. injection: ↑ PROK2, PKR1 and PKR2 mRNA and protein in prefrontal cortex and hippocampus (Severini et al, 2015;Lattanzi et al, 2019;Maftei et al, 2019) -PKRs antagonist: ↓ PROK2 levels, ↓ glial activation and neuronal death, restores the neurogenesis in DG and ↓ the Aβ-induced memory deficits (Maftei et al, 2019) -AD patients -↑ PROK2 mRNA in hippocampus and ↑ PROK2 protein in serum (Lattanzi et al, 2019) Glutamate Neurotoxic -Primary cortical cell cultures -NMDA and excitotoxic glutamate: ↑ PROK2 mRNA mainly in neurons…”
Section: Pathological Insult Prok2 Activity Experimental Model Resultsmentioning
confidence: 99%
“…The excessive accumulation of lipids can directly lead to the imbalance between the production and clearance of reactive oxygen species, which is the occurrence of oxidative stress reaction. Studies have shown that reducing ROS production protects cardiomyocytes damaged by glycolipid toxicity ( Kolleritsch et al, 2020 ; Yang et al, 2020 ). In our study, AuCur successfully reduced the accumulation of lipid droplets and the increase of ROS in cardiomyocytes due to high lipid levels.…”
Section: Discussionmentioning
confidence: 99%